The Facebook's Effect: Usage Of Social Media In Teaching English Reading Skills For Secondary Schools' Students In Abu Dhabi City (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the effects of Facebook usage on advancing the reading skills of English versus the conventional methods of teaching for grade ten students. A conventional sample of eighty students were selected and divided into two groups (40 experimental and 40 controls). For 12 weeks, the control group studied English conventionally while experimental group studied via Facebook. The students were seated for a pre and post English test to compare results. The post test result test for the experimental group scored an average of 32.38, SD 15.60 while the control group in the same posttest scored an average of 13.31 SD 8.81, the t test was 6.382 and the significance level was 0.000 and ETA square h2 of (0.34). The result showed a statistically significant difference in favor of Facebook as it shows improvement in reading skills for the experimental group more than the conventional method.